A simple and fast procedure for fenoxycarb determination in pesticide formulations based on infrared spectrometry - Quintás, Guillermo; Armenta, Sergio; Garrigues, Salvador; de la Guardia, Miguel (Ciencia)
A fast and environmentally friendly procedure has been developed for Fenoxycarb determination in pesticide formulations by FTIR spectrometry. The method is based on an off-line extraction of the pesticide and stopped-flow measurement of the mid-IR spectra from 4000 to 850 cm-1 using a nominal resolution of 4 cm-1 and accumulating 25 scans. Fenoxycarb was determined using peak area measurements from 1509 to 1499 cm-1 corrected using a two points baseline defined between 1570 and 1403 cm-1. The proposed procedure has been compared with a reference chromatographic method. Results obtained by FTIR were statistically comparable to those found by HPLC. The developed method provided a LOD of 14 Âµg g-1, corresponding to 0.2 % (w/w) Fenoxycarb in the original sample and a sampling frequency of 60 h-1 with a waste generation of 3 mL CHCl3 for each sample. So, involving a reduction of organic solvent consume as compared with the HPLC method, which requires 55 mL CH3CN per sample, and a 6 times faster alternative than HPLC, which has a sampling frequency of 10 h-1.